Unpacking the Role of Feedback in Virtual Team Effectiveness - Handke, Lisa; Klonek, Florian; O’Neill, Thomas A.; Kerschreiter, Rudolf (Small Group Research, 2022)
Feedback is a cornerstone of human development. Not surprisingly, it plays a vital role in team development. However, the literature examining the specific role of feedback in virtual team effectiveness remains scattered. To improve our understanding of feedback in virtual teams, we identified 59 studies that examine how different feedback characteristics (content, source, and level) impact virtual team effectiveness. Our findings suggest that virtual teams benefit particularly from feedback that (a) combines performance-related information with information on team processes and/or psychological states, (b) stems from an objective source, and (c) targets the team as a whole. By integrating the existing knowledge, we point researchers in the direction of the most pressing research needs, as well as the practices that are most likely to pay off when designing feedback interventions in virtual teams.
CRIS-Team Scopus Importer:2023-09-18
Keywords: computer-mediated communication; feedback; teamwork; virtual groups